Prove that $\cos ^{2} 2 x-\cos ^{2} 6 x=\sin 4 x \sin 8 x$
It is known that
$\cos A+\cos B=2 \cos \left(\frac{A+B}{2}\right) \cos \left(\frac{A-B}{2}\right), \cos A-\cos B=-2 \sin \left(\frac{A+B}{2}\right) \sin \left(\frac{A-B}{2}\right)$
$\therefore$ $L.H.S.$ $=\cos ^{2} 2 x-\cos ^{2} 6 x$
$=(\cos 2 x+\cos 6 x)(\cos 2 x-6 x)$
${ = \left[ {2\cos \left( {\frac{{2x + 6x}}{2}} \right)\cos \left( {\frac{{2x - 6x}}{2}} \right)} \right]}$
${\left[ { - 2\sin \left( {\frac{{2x + 6x}}{2}} \right)\sin \left( {\frac{{2x - 6x}}{2}} \right)} \right]}$
${ = [2\cos 4x\cos ( - 2x)][ - 2\sin 4x\sin ( - 2x)]}$
${ = [2\cos 4x\cos 2x][ - 2\sin 4x( - \sin 2x)]}$
${ = (2\sin 4x\cos 4x)(2\sin 2x\cos 2x)}$
${ = \sin 8x\sin 4x = R.H.S}$
$\frac{{\sin 3A - \cos \left( {\frac{\pi }{2} - A} \right)}}{{\cos A + \cos (\pi + 3A)}} = $
$\frac{{\tan A + \sec A - 1}}{{\tan A - \sec A + 1}} = $
If $\sin \theta + \cos \theta = x,$ then ${\sin ^6}\theta + {\cos ^6}\theta = \frac{1}{4}[4 - 3{({x^2} - 1)^2}]$ for
${\sin ^4}\frac{\pi }{8} + {\sin ^4}\frac{{3\pi }}{8} + {\sin ^4}\frac{{5\pi }}{8} + {\sin ^4}\frac{{7\pi }}{8} = $
$\sin 4\theta $ can be written as